USE OF BIOLOGICAL REMEDIATION IN ANAEROBIC BIO-DIGESTION OF THE POULTRY LITTER - DA COSTA, L. V. C.; SAGULA, A. L.; JÚNIOR, J. L. (Revista Brasileira de Engenharia de Biossistemas, 2012)
The poultry litter byproduct generated in the production of broilers, is being increasingly reused by producers, and this poultry litter often composed of products available in a given region, such as sugarcane bagasse, peanut shell, rice husk etc., these products classified as highly lignified and difficult to degrade, especially when working with treatment in anaerobic digestion, hindering the performance of methanogenic bacteria. Based on this situation, the objective of this study was to evaluate the inclusion of biological remediation in anaerobic digestion of poultry litter t had or not the separation of the solid and liquid phase and its effect on yield and quality of biogas. 12 model batch digesters bench stocked with poultry litter 3rd batch of reuse and commercial biological remediation were used. The hydraulic retention time was 120 days. It was observed that the treatments did not have the separation of solids added to biological remediation were most likely produced biogas, and the percentage of methane by means did not differ between treatments.